Change in the Single Amino Acid Site 83 in Rabies Virus Glycoprotein Enhances the BBB Permeability and Reduces Viral Pathogenicity - Li, Chunfu; Wang, Yongzhi; Liu, Huiting; Zhang, Xinghua; Baolige, Dalai; Zhao, Shihua; Hu, Wei; Yang, Yang (Frontiers in Cell and Developmental Biology, 2021)
Lab-attenuated rabies virus (RABV) is a highly cellular adaptation and less pathogenic than wild-type RABV. However, the molecular mechanisms that regulate the cellular adaptation and pathogenicity remain obscure. In this work, we isolated a wild-type RABV (CNIM1701) from a rabid bovine in northern China. The original CNIM1701 was lethal in adult mice and restricted replication in cell cultures. After 20 serial passages in the brains of suckling mice, the virus was renamed CNIM1701-P20, which was safe in adult mice and replicated well in cell cultures. In addition, sequence comparison analysis of the original CNIM1701 and CNIM1701-P20 identified 2 amino acid substitutions on G protein (Lys83 → Arg83 and Pro367 → Ser 367) related to pathogenesis and cellular adaptation. Using site-directed mutagenesis to exchange Lys83 with Arg83 and Pro367 with Ser 367 in the G protein of the RABV SAD strain, the pathogenicity of rSAD-K83R was significantly decreased. Our data indicate that the decreased pathogenicity of rSAD-K83R is due to increasing the expression of RABV-G, which also induced a higher level of apoptosis in infected cells. Furthermore, the K83 mutation induced high expression of MMP-2 and MMP-9 on DCs and promoted blood–brain barrier (BBB) permeability. These results demonstrate that the pathogenesis of RABV is partially dependent on G expression and BBB permeability, which may help in the design and development of highly safe, live-RABV vaccines.